2008
DOI: 10.2217/14796708.4.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Aspects of Varicella Zoster Virus Infection

Abstract: SummaryA declining cell-mediated immunity to varicella zoster virus (VZV) with advancing age or immunosuppression results in virus reactivation from latently infected human ganglia anywhere along the neuraxis. Virus reactivation produces zoster, often followed by chronic pain (postherpetic neuralgia or PHN) as well as vasculopathy, myelopathy, retinal necrosis and cerebellitis. VZV reactivation also produces pain without rash (zoster sine herpete). Vaccination after age 60 reduces the incidence of shingles by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 154 publications
(136 reference statements)
0
27
0
Order By: Relevance
“…Biological plausibility is based on the ability of the varicella zoster virus to remain latent for decades after the primary infection in the cranial nerve, dorsal root, and autonomic ganglia along the entire neuroaxis (12). In addition, studies have revealed that reactivation of the latent virus is not necessarily accompanied by cutaneous outbreaks (13) and can occur at any period in life, most commonly in individuals older than 50 years and those with suppressed cellular immunity (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Biological plausibility is based on the ability of the varicella zoster virus to remain latent for decades after the primary infection in the cranial nerve, dorsal root, and autonomic ganglia along the entire neuroaxis (12). In addition, studies have revealed that reactivation of the latent virus is not necessarily accompanied by cutaneous outbreaks (13) and can occur at any period in life, most commonly in individuals older than 50 years and those with suppressed cellular immunity (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] 2. Clinical diagnosis of VZV neurologic disorders is confirmed by virologic analysis with the detection of VZV DNA or anti-VZV immunoglobulin G (IgG) antibody in the CSF.…”
Section: Cns Complications Of Varicella-zoster Virus (Vzv)mentioning
confidence: 99%
“…Subsequently, later in life, and as specific cell-mediated immunity to the virus declines with age or immunosuppression, VZV reactivates to cause shingles, often followed by postherpetic neuralgia, vasculopathy, myelopathy, retinal necrosis and cerebellitis. 3 The epidemiology of varicella exhibits significant differences in temperate and tropical regions. 4 In temperate locations, varicella primarily affects children 5 ; however, in tropical areas, varicella tends to occur at a later age, during adolescence and adulthood, with an increased risk of developing a more severe disease.…”
Section: Introductionmentioning
confidence: 99%